Implementasi Metode ARAS Pengangkatan Kepala Unit Pelaksana Teknisi Badan Pengelola Pajak Dan Retribusi Daerah - Sibuea, Dhea Nita (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Badan Pengelola Pajak dan Retribusi Daerah UPT Medan Utara is one of the governments that operates in the field of local revenue, one of which is the Motor Vehicle Tax (PKB). Motor vehicle tax is calculated based on the type of vehicle, brand, vehicle type, year of manufacture, pollution level based on the fuel used, cc, or cylinder content, and the color of the vehicle number mark (TNKB). Motor vehicle tax collection carried out in one office is known as SAMSAT (One Roof Single Administration System), in which there is cooperation between the Indonesian National Police (POLRI) which has functions and authorities in the field of registration and identification of motorized vehicles, local governments in this case the Regional Tax and Retribution Management Agency in the field of motor vehicle tax collection (BBN-KB), PT Jasa Raharja (Persero) which is authorized in the field of submission of Mandatory Contributions to Road Traffic Accident Funds (SWDKLLJ). This study aims to analyze the implementation of the Appointment of the Head of the Technical Unit in the management of Motor Vehicle Tax at the North Medan UPT Regional Tax and Retribution Management Agency. This research uses descriptive qualitative research methods. Data collection procedures used with interviews, observation, documentation. Data analysis is done by data reduction, data presentation and conclusion drawing. By carrying out coordination, cooperation with related parties, coaching technical control and evaluation, extracting potential, empowering potential and collecting regional revenue sources in accordance with applicable regulations.